Backstepping Control Strategy For An Underactuated X4-AUV - Zainah, Md. Zain; Nur Fadzillah, Harun (Penerbit Universiti Teknologi Malaysia, 2015)

(untitled)
A nonlinear control method is considered for stabilizing all attitudes and positions (x, y or z) of an underactuated X4-AUV with four thrusters and six degrees-of-freedom (DOFs), in which the positions are stabilized according to the Lyapunov stability theory and angles are stabilized using backstepping control method. A dynamical model is first derived, and then a sequential nonlinear control strategy is implemented for the X4-AUV, composed of translational and rotational subsystems. A controller for the translational subsystem stabilizes one position out of x-, y-, and z-coordinates, whereas controllers for the rotational subsystems generate the desired roll, pitch and yaw angles. Thus, the rotational controllers stabilize all the attitudes of the X4-AUV at a desired (x-, y- or z-) position of the vehicle. Some numerical simulations are conducted to demonstrate the effectiveness of the proposed controllers.